2017 Joint IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL-EpiRob) 2017
DOI: 10.1109/devlrn.2017.8329832
|View full text |Cite
|
Sign up to set email alerts
|

Iterative affordance learning with adaptive action generation

Abstract: Abstract-A robot designer can provide a robot with knowledge to perform tasks on an environment. However, this approach can limit the achievement of future tasks executed by the robot. Providing it with the ability to develop its own skills paves the way for robots that are not limited by design. In this work a task consists in reproducing a given set of effects on an object. A robot must accomplish this task with limited information about the object, learning affordances to reproduce the effects, increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The skill was implemented as a Bayesian Network (BN). In our previous work (Maestre et al, 2017) we identified a task-agnostic BN structure useful for the action generation. Therefore, building the skill consists in learning the Conditional Probabilistic Distributions (CPDs) of the BN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The skill was implemented as a Bayesian Network (BN). In our previous work (Maestre et al, 2017) we identified a task-agnostic BN structure useful for the action generation. Therefore, building the skill consists in learning the Conditional Probabilistic Distributions (CPDs) of the BN.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, the structure represents the knowledge that an interaction is based on the relative position of the end-effector and an object, and the actual values of the interaction are stored as CPDs. In our previous work (Maestre et al, 2017) a simulated Baxter robot executed an exploration of a static environment identifying the BN structure and CPDs to push an object in different directions. The results demonstrated that the BN structure is task- and environment-agnostic.…”
Section: Interaction State-based Skill Learning (Is2l)mentioning
confidence: 99%
See 1 more Smart Citation
“…Robots operating in the real, unstructured world may understand available opportunities conditioned on their body, perception and sensorimotor experiences: the intersection of these elements gives rise to object affordances (action possibilities), as they are called in psychology [37]. The advantage of robot affordances lies in the ability to capture essential functional properties of environment objects in terms of the actions that the agent is able to perform with them, allowing to reason with prior knowledge about never-before-seen scenarios, thus exhibiting learning [38], [39] and some degree of online adaptation [40].…”
Section: Related Workmentioning
confidence: 99%